Analysis of Translation Strategies for Mandarin Culture-Specific Items into English in Cultural Promotional Texts - Mei Lisa; Elly Romy; Wenny; Ivana; Kevin Utama (ELT (English Language Teaching Prima Journal), 2026)
This study examines translation strategies for Mandarin culture-specific items (CSIs) in Chinese official cultural promotional texts, motivated by the growing role of digital cultural diplomacy in projecting national identity to international audiences. Using a qualitative descriptive approach, 312 CSIs were collected from 24 bilingual documents published by Chinese government agencies and cultural institutions (2021–2024). Analysis integrated Aixelá’s CSI framework, Newmark’s cultural taxonomy, Baker’s strategies, Venuti’s foreignization/domestication, and Nababan et al.’s quality assessment model (accuracy, acceptability, readability). Findings show that cultural equivalent is the most frequent strategy, while transference is reserved for highly unique CSIs to preserve source-culture identity. A clear relationship emerged between CSI characteristics, strategy choice, orientation, and translation quality: terms with established English equivalents are rendered via cultural equivalent with domestication, whereas culturally loaded terms favor transference with foreignization. This study offers an integrative analytical framework that advances Translation Studies theory and provides practical guidance for translating cultural promotional materials, thereby supporting effective intercultural communication and digital cultural diplomacy